KONDISI HUTAN MANGROVE DITELUK AMBON: PROSPEK DAN TANTANGAN - Suyadi Suyadi (BERITA BIOLOGI, 2009)
The destruction of mangrove forest constitutes one of the greatest threats to biodiversity and conservation of Ambon Bay.But,data and information of condition and potential of mangrove in Ambon Bay are lacking. We link three methods: remote sensing,Biological survey using transect, and sedimentation sampling to study the condition and potential of mangrove in Ambon Bay specially for biodiversity and sediment trapped. Remote sensing data showed that area of mangrove forest in Ambon Bay 34 ha and has declined dramatically in the past decade.The research recorded 8 species of mangrove; two are recorded as new species compared to the last survey.Based on data collected from four transects, mangrove forest in Ambon Bay is habitat for 8 species of mollusc and species of fish, crustacean, bird and epiphytes. Sediment analysis showed that mangrove forest 80% more effective to reduce sediment that come in to Ambon bay. Finally, the result indicated that condition of mangrove forest in Ambon Bay has been declined, nevertheless, have great potential for conservation of biodiversity and efficient in trapping sediment that come in to Ambon Bay.